1993
DOI: 10.1063/1.353936
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of electrical properties on film thickness in Pb(ZrxTi1−x)O3 thin films produced by metalorganic chemical vapor deposition

Abstract: Strongly c-axis oriented Pb(ZrxTi1−x)O3 (PZT) thin films with tetragonal perovskite structure (0.45≤x≤0.52) were epitaxially grown on (100)Pt/(100)MgO substrates using metalorganic chemical vapor deposition. Film thickness could be varied by altering the growth time. The electrical properties of PZT thin films sharply change below a thickness of 0.5 μm: the dielectric constant and remanent polarization decrease while the coercive field increases. These phenomena are explained by a model in which a layer with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(73 citation statements)
references
References 17 publications
9
58
1
1
Order By: Relevance
“…This results are contrary to the reports of piezoelectric ͑PZT͒ films, where the electrical properties of PZT films strongly depend on thickness in the thickness range from 25 to 300 nm. [6][7][8]11,12 The films with thickness of 50-500 nm showed similar AFM microstructure. Figure 2 shows the AFM microstructure of the 80 nm film.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…This results are contrary to the reports of piezoelectric ͑PZT͒ films, where the electrical properties of PZT films strongly depend on thickness in the thickness range from 25 to 300 nm. [6][7][8]11,12 The films with thickness of 50-500 nm showed similar AFM microstructure. Figure 2 shows the AFM microstructure of the 80 nm film.…”
Section: Resultsmentioning
confidence: 82%
“…The low dielectric constant interfacial layers results in a decrease in the effective dielectric constant and remanent polarization, and increase in loss tangent and coercive field of the entire film. [12][13][14] The other model is based on the domain structure transition from multidomain predominance to single domain predominance at a critical grain size in the thin film. 19 The lack of the domain walls and the low domain wall mobility in the single domain predominated film, usually associated with small grains, may induce the size effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MOD is one of the considerable deposition methods, since it is a non-gelling chemical process in which molecular homogeneity is attained in the liquid phase, and the solutions can be produced without solution gelling and at a lower processing temperature 5 . Few reports have shown that the microstructural charactheristics and electrical properties of PZT thin films depend greatly on the annealing temperature 8 and film thickness [9][10][11] , however little has been done in regard to the dependence of ferroelectric properties and fracture toughness on annealing procedure. It is known that ferroelectric and mechanical properties of thin film including remanent polarization, coercive field, fracture toughness, residual stress and hardness are very important parameters, which will be used to the design of the film/substrate system.…”
Section: Introductionmentioning
confidence: 99%